Fostering Creativity and Innovation: A Study of Bachelor of Science in Hospitality Management Faculty in the West Visayas State University System - Mapa, Ma Nellie; Jocson, Joy D; Oquendo, Ann Cristine (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This descriptive research design examined the level of creativity and innovation in the teaching practices of Bachelor of Science in Hospitality Management faculty within the West Visayas State University System for the Academic Year 2022-2023.The respondents were the total enumeration of 55 faculty members from among the Main Campus and Satellite Campuses of the whole university system.  A researcher-made instrument was used in gathering the data. The instrument underwent validation using Cronbach alpha. Descriptive statistical tools, frequency count and percentage were used to describe profile of the respondents while mean was used to describe the level of creativity and innovativeness. Non-parametric Mann Whitney U test and Kruskall Wallis H test were used to determine for differences and Spearman Rho was used to determine the relationship among creativity and innovativeness set at .05 level of significance.Results revealed that business and hospitality management faculty of WVSU were very highly creative and very highly innovative. There were no significant differences in the level of creativity, in terms of age, sex, civil status, educational attainment, academic rank, length of service and campus. There were no significant differences in the level of innovativeness of faculty members in terms of age, sex, civil status, educational attainment, academic rank, length of service and campus. There were significant differences in the level of creativity and innovativeness in terms of sex. There were significant differences in the level of creativity and innovativeness in terms of civil status. The level of creativity has significant positive influence on innovativeness of the business management faculty of the West Visayas State University.